Three-dimensional steering for an articulated mobile robot with prismatic joints with consideration of hardware limitations. (2nd June 2020) - Tanaka, Motoyasu; Nakajima, Mizuki; Ariizumi, Ryo; Tanaka, Kazuo
ABSTRACT: The paper presents a three-dimensional steering method for an articulated mobile robot that contains links, rotational joints, prismatic joints, and active wheels. The robot can change the angles of its links using the rotational joints and vary the lengths of its links using the prismatic joints. The target motion of this robot is represented by a continuous curve and the motions of the joints and the wheels are calculated by fitting the entire robot to this target curve. The forward velocity of the robot's head is adjusted to satisfy the hardware limitations of the robot; e.g. joint angle, joint velocity, and wheel velocity limitations. In addition, a terrain-following method is presented that considers the changes in the lengths of the links. An experimental articulated mobile robot was developed and experiments were carried out to demonstrate the effectiveness of the proposed method. GRAPHICAL ABSTRACT: UF0001